2013
DOI: 10.1093/mnras/stt1891
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of dark matter profiles on the stellar-to-halo mass ratio: a prediction for cusps versus cores

Abstract: We use a suite of 31 simulated galaxies drawn from the MaGICC project to investigate the effects of baryonic feedback on the density profiles of dark matter haloes. The sample covers a wide mass range: 9.4 × 10 9 < M halo /M ⊙ < 7.8 × 10 11 , hosting galaxies with stellar masses: 5.0 × 10 5 < M ⋆ /M ⊙ < 8.3 × 10 10 , i.e. from dwarf to L ⋆ . The galaxies are simulated with blastwave supernova feedback and, for some of them, an additional source of energy from massive stars is included. Within this feedback sch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
491
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(554 citation statements)
references
References 71 publications
60
491
1
2
Order By: Relevance
“…It requires a heavy stellar disk at the limit of the range allowed by our mass maps. The presence of a dark cuspy core in M 33, as predicted by structure formation in a ΛCDM hierarchical universe, is in agreement with numerical simulation of baryonic feedback effects on the density profile of dark matter (Di Cintio et al 2014b). For our best fit halo mass, energy from stellar feedback is insufficient to significantly alter the inner dark matter density, and the galaxy retains a cuspy profile.…”
Section: Discussionsupporting
confidence: 83%
“…It requires a heavy stellar disk at the limit of the range allowed by our mass maps. The presence of a dark cuspy core in M 33, as predicted by structure formation in a ΛCDM hierarchical universe, is in agreement with numerical simulation of baryonic feedback effects on the density profile of dark matter (Di Cintio et al 2014b). For our best fit halo mass, energy from stellar feedback is insufficient to significantly alter the inner dark matter density, and the galaxy retains a cuspy profile.…”
Section: Discussionsupporting
confidence: 83%
“…As we discussed [8], these limits are subject to large astrophysical uncertainties, and a sufficiently large, > 1 kpc, core can be invoked to reconcile the wino with experiment. However, we see that the situation is qualitatively unchanged from our earlier result, and saving the wino requires a profile in tension with current results from simulation [14][15][16].…”
Section: Jhep03(2016)213contrasting
confidence: 74%
“…We found the overall correction from resummed double logs to be modest, with a few percent reduction in the cross section at the relic density mass of 3 TeV relative to tree level (+ Sommerfeld enhancement). Thus, the factor of ∼ 15 exclusion by HESS remained, unless one invoked a profile with coring 1.5 kpc, in tension with recent simulations [14][15][16].…”
Section: Jhep03(2016)213mentioning
confidence: 81%
“…Di Cintio et al (2014a) found that the inner dark matter density slope, α, was more strongly correlated with ǫSF, than galaxy or halo mass. At very low efficiencies, there is no change with α ≈ 1.2 as would be expected.…”
Section: Introductionmentioning
confidence: 99%